What do patients ask when using a medicines helpline service?. Issue 7 (4th September 2020) - Robertson, Adrian J; Forkin, Deborah; Astin, Felicity
Abstract : A medicines helpline service, run by a hospital pharmacy department, is one intervention that may help reduce medication errors and improve patient safety. Here, the authors describe their study examining how patients utilise Mid Yorkshire Hospitals NHS Trust's medicines helpline service, in terms of the types of enquiries received and how these relate to the medicines dispensed within the Trust. They also discuss how the service could be improved.